Brunner on the state of international monetary policy - R. SOLOMON (PSL Quarterly Review, 2013)
This brief note serves as a response to Karl Brunner’s characterisation of the author’s views on the Bretton Woods system. The author also raises some questions about Brunner’s interpretation of post-World War II international monetary developments.